Talleres de Fotografía social: Puno: Una mirada a través de los siglos - Autores, Varios (1991)
The photos selected here have been taken by popular photographers, most of them peasants from the Ayaviri Social Photography Workshop, who have been working for three years on the graphic documentation of their reality and on communication actions. They thus show us, from their point of view as actors and leaders of popular organizations, a different and peculiar way of capturing their environment and their problems.